Interfacial Behavior of Thin Ionic Liquid Films on Mica - Deyko, A; Cremer, T; Rietzler, F; Perkin, S; Crowhurst, L; Welton, T; Steinrueck, H; Maier, F (2013)
Ultrathin films of two imidazolium-based ionic liquids (ILs), [C 1C1Im][Tf2N] (=1-methyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) and [C4C1Im][Tf 2N] (=1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) were deposited on mica surfaces by physical vapor deposition in ultrahigh vacuum. Using angle-resolved X-ray photoelectron spectroscopy (ARXPS), the initial wetting behavior, the growth characteristics, and the molecular arrangement of the ions at the interface were investigated. The measurements were performed on freshly air-cleaved mica surfaces with different carbon precoverages. ARXPS clearly reveals that the initial IL adsorption behavior strongly depends on the amount of preadsorbed carbon: On clean mica, 3D growth (complete dewetting) occurs, whereas on a fully carbon covered surface, initially a complete 2D wetting layer forms, followed by 3D growth. © 2013 American Chemical Society.